Bifurcation physics of magnetic islands and stochasticity explored by heat pulse propagation studies in toroidal plasmas. (29th July 2016) - Ida, K.; Kobayashi, T.; Yoshinuma, M.; Suzuki, Y.; Narushima, Y.; Evans, T.E.; Ohdachi, S.; Tsuchiya, H.; Inagaki, S.; Itoh, K.
Abstract: Bifurcation physics of a magnetic island was investigated using the heat pulse propagation technique produced by the modulation of electron cyclotron heating. There are two types of bifurcation phenomena observed in a large helical device (LHD) and DIII-D. One is a bifurcation of the magnetic topology between nested and stochastic fields. The nested state is characterized by the bi-directional (inward and outward) propagation of the heat pulse with slow propagation speed. The stochastic state is characterized by the fast propagation of the heat pulse with electron temperature flattening. The other bifurcation is between the magnetic island with larger thermal diffusivity and that with smaller thermal diffusivity. The damping of toroidal flow is observed at the O-point of the magnetic island both in helical plasmas and in tokamak plasmas during a mode locking phase with strong flow shears at the boundary of the magnetic island. Associated with the stochastization of the magnetic field, the abrupt damping of toroidal flow is observed in LHD. The toroidal flow shear shows a linear decay, while the ion temperature gradient shows an exponential decay. This observation suggests that this flow damping is due to the change in the non-diffusive term of momentum transport.